Experimental investigation on compressive strength and chloride permeability of fiber-reinforced concrete with basalt-polypropylene fibers. Issue 10 (July 2019) - Niu, Ditao; Huang, Daguan; Fu, Qiang
This article presents the effects of basalt-polypropylene fibers on the compressive strength and chloride ion resistance of concrete with matrix strength grades C30, C40, and C50. Test results indicated that hybrid fibers can effectively improve the compressive strength of concrete; that the maximum increases in compressive strength of C30, C40, and C50 concrete were 9.18%, 5.06%, and 7.13%, respectively; and that the effect of basalt fiber on compressive strength was greater than that of polypropylene fiber. A suitable quantity of hybrid fibers can effectively improve the chloride ion resistance of concrete. The enhancement was greatest for C50 concrete, in which the chloride diffusion coefficient was reduced by 77.8% compared to the reference concrete. The chloride diffusion coefficient of basalt-polypropylene fiber–reinforced concrete has a strong positive correlation with the coulomb electric flux. However, the hybrid fibers have adverse effects on the compressive strength and chloride ion resistance of concrete when the quantity of fibers is excessive. Therefore, considering the compressive strength and chloride ion resistance of concrete, the total volume fraction of hybrid fibers should not exceed 0.15%.